Top Challenges Facing the Florida Strawberry Industry: Insights from a Comprehensive Industry Survey - Zhengfei Guan; Feng Wu; Alicia Whidden (EDIS)
Florida is the largest supplier of winter strawberries in the United States and the second largest overall after California. The farm-gate value of Florida strawberries is approximately US$400 million and the total economic contribution of the industry is estimated at about US$1 billion. Even so, over the last few years, the Florida strawberry industry has faced many challenges. In 2012, Florida production was down by 20% compared to the previous year. The record level of imports of strawberries from Mexico deeply depressed the market, causing a market crash at the peak season of the Florida production. Decreased revenues coupled with increased production costs have caused significant losses to the Florida industry. In this 3-page article, Zhengfei Guan, Feng Wu, and Alicia Whidden investigate Florida growers’ perceptions of various threats and challenges and discuss those threats that should be dealt with as high priority. Published by the UF Food and Resource Economics Department, November 2015.